Analysis of the Impact of External Shocks on the Profitability of the Assets of Economic Entities of Ukraine - Motoryn R. М.; Prykhodko К. R.; Prykhodko, M. R. (Statistics of Ukraine, 2024)
The article analyzes the analytical capabilities of asset profitability ratios, which are constructed on the basis of net profit, profit before interest and taxes (EBIT), and profit before interest, taxes and depreciation of fixed assets and intangible assets (EBITDA). As a result, the indicator of profitability of total assets was chosen. Practical recommendations on the analysis of the profitability of assets have been developed depending on the goals of the analysis and the need to take into account the industry structure of assets. For this purpose, it is proposed to evaluate the structural shifts of aggregate assets and the profitability of assets based on the use of so-called integral coefficients: the linear coefficient of absolute structural shifts, the quadratic coefficient of absolute structural shifts, and the integral coefficient of Gatev’s structural shifts. Empirical economic and statistical analysis of the impact of COVID-19 and the military aggression of the Russian Federation on the profitability of the assets of business entities of Ukraine was conducted according to the data of the State Statistics Service of Ukraine. The information base of the empirical analysis was also data from the financial statements of Ukrainian enterprises for 2019–2022. Calculations were made using the Excel program. An analysis of the profitability of the total assets of active economic entities of Ukraine in the 2019–2022 period by industry was made. It has been proven that the COVID-19 pandemic had a significant impact on all sectors of Ukraine. For half of the industries, 2020 was unprofitable. During the period from 2019 to 2020, the rate of return on the total assets of active business entities of Ukraine increased only in the field of health care and social assistance, which is natural for the active phase of the COVID-19. In 2022, compared to 2021, there were even more significant changes in the sectoral structure of the profitability of assets of active business entities of Ukraine. The main reason for such negative changes was the military aggression of the Russian Federation. In 2022, negative profitability indicators were already observed in 11 out of 18 industries. The direction of further research is outlined.